Elucidating the Genetic Architecture of Fiber Quality in Hemp (Cannabis sativa L.) Using a Genome-Wide Association Study - Petit, Jordi; Salentijn, Elma M. J.; Paulo, Maria-João; Denneboom, Christel; van Loo, Eibertus N.; Trindade, Luisa M. (Frontiers in Genetics, 2020)
Hemp (Cannabis sativa L.) is a bast-fibre crop with a great potential in the emergent bio-based economy. Yet, hemp breeding for fibre quality is restricted and that is mainly due to the limited knowledge of the genetic architecture of its fibre quality. A panel of 123 hemp accessions, with large phenotypic variability, was used to study the genetic basis of seven cell wall and bast fibre traits relevant to fibre quality. These traits have large genetic variance components and broad-sense heritabilities in this hemp panel, as concluded from the phenotypic evaluation across three test locations with contrasting environments. The hemp panel was genotyped using Restriction site Associated DNA Sequencing (RAD-seq). Subsequently, a large set (>600,000) of selected genome-wide SNP markers was used for a Genome-Wide Association Study (GWAS) approach to get insights into quantitative trait loci (QTL) controlling fibre quality traits. In absence of a complete hemp genome sequence, identification of QTLs was based on the following characteristics: i. association level to traits, ii. fraction of explained trait variance, iii. collinearity between QTLs and iv. detection across different environments. Using this approach, 16 QTLs were identified across locations for different fibre quality traits, including contents of glucose, glucuronic acid, mannose, xylose, lignin and bast fibre content. Among them, six were found across the three environments. The genetic markers composing the QTLs that are common across locations are valuable tools to develop novel genotypes of hemp with improved fibre quality. Underneath the QTLs, twelve candidate genes were identified which are likely to be involved in the biosynthesis and modification of monosaccharides, polysaccharides and lignin. These candidate genes were suggested to play an important role in determining fibre quality in hemp. This study provides new insights into the genetic architecture of fibre traits, identifies QTLs and candidate genes that form the basis for molecular breeding for high fibre quality hemp cultivars.